A Pilot Study on the Cutoff Value of Related Brain Metabolite in Chinese Elderly Patients With Mild Cognitive Impairment Using MRS - Zhao, Lihua; Teng, Jinlong; Mai, Wei; Su, Jiahui; Yu, Bihan; Nong, Xiucheng; Li, Chong; Wei, Yichen; Duan, Gaoxiong; Deng, Xiangming; Deng, Demao; Chen, Shangjie (Frontiers in Aging Neuroscience, 2021)
ABSTRACT Objective: In this cross-sectional study, our aim was to distinguish MCI patients from normal controls by measuring NAA, tCr and Cho levels in the hippocampus (HIP) and posterior cingulate gyrus (PCG) of control and MCI patients by using proton magnetic resonance spectroscopy (MRS), and to predict the cut-off value on metabolite ratios. To provide a reference for the diagnosis of MCI in the elderly in China. Methods: 69 patients with clinical diagnosis of MCI group and 67 normal controls (NC), Mini-Mental Status Examination (MMSE), Montreal Cognitive Assessment (MoCA) scores and magnetic resonance spectroscopy (MRS) of bilateral HIP and PCG were measured. The ratio of N-acetyl aspartate/ total creatine (NAA/tCr) and choline /creatine (Cho/tCr) in bilateral HIP and PCG were calculated. The relationship between the ratio of metabolites and the scores of MMSE and MoCA were analyzed, and to evaluate the possible brain metabolite cut-off point for the diagnosis of mild cognitive impairment. Results: Compared with NC group, the scores of MMSE and MoCA in MCI group decreased significantly (P<0.05), the ratio of NAA/tCr in bilateral HIP and PCG, the ratio of Cho/tCr at right HIP in MCI group decreased significantly (P<0.05), but there was no significant difference in the ratio of Cho/tCr at left HIP and bilateral PCG between the two groups (P>0.05). The correlation coefficient between MMSE/MoCA and the ratio of NAA/tCr were 0.49-0.56 at the bilateral HIP (P<0.01).The best cutoff values of the left and right HIP (NAA/Cr) were 1.195 and 1.19. The sensitivity, specificity and Youden index were (0.725, 0.803, 0.528), (0.754, 0.803, 0.557). Conclusion: The level of metabolites in HIP and PCG of MCI patients and normal subjects has a certain correlation with their MMSE and MoCA scores. When the NAA/tCr value of left and right HIP is lower than 1.19, it suggests that mild cognitive impairment may have occurred. According to this cut-off point, MCI patients in the elderly in China could be screened. Keywords: N-acetyl aspartate; creatine; choline hippocampus; posterior cingulate gyrus; mild cognitive impairment